Lectio e Qua Caeterarum Ortus facillime explicetur - Hendriks, Wim (Filología neotestamentaria, 2009)
More than once a great number of different readings of the same text can be found. If one wants to find the authentic text, one should look according to Griesbach for the reading 'e qua caeterarum ortus facillime ex plicetur', the reading that easily explains the rise of the others. However, textual criticism involves more than simply determ ining the original text. It also entails seeing how that text came to be modified over time. In addition, one may think of the efforts of Amphoux who distinguishes several 'editions' of the gospels before the text of the great uncials of the fourth century. In this study I will expose my method and illustrate my way of handling textual variants by five texts from the first chapter of the gospel of Mark. The Bezan Codex D.05 is evidently an important witness for this gospel.